1976
DOI: 10.1073/pnas.73.5.1398
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance studies of slowly exchanging peptide protons in cytochrome c in aqueous solution.

Abstract: The slowly exchanging protons in oxidized and reduced horse heart cytochrome c (D20, uncorrected pH meter reading 6.5, room temperature) have been monitored by recording the 270 and 360 MHz proton nuclear magnetic resonance spectra of the reduced protein between 5 and 11 parts per million downfield from 2,Aimethyl-2-silapentane-5-sulfonate.There are about 12 well-resolved exchangeable resonances between 7.9 and 10.1 parts per million and the experimental chemical shift data suggest that they originate from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…However, both X-ray and NMR solution structures clearly indicated that the two states are virtually identical . Thus, the observed differences in rates of proteolysis, radius of gyration, ligand binding, and H/D isotope exchange, along with the negative entropy of reduction, , led to the conclusion that the oxidized state was more flexible and thus sampled a wider range of conformational substates than the reduced protein . The increased rigidity of the reduced protein was also soon linked to an increase in the strength of the Met80 S–Fe bond relative to the oxidized state .…”
Section: Case Studiesmentioning
confidence: 99%
“…However, both X-ray and NMR solution structures clearly indicated that the two states are virtually identical . Thus, the observed differences in rates of proteolysis, radius of gyration, ligand binding, and H/D isotope exchange, along with the negative entropy of reduction, , led to the conclusion that the oxidized state was more flexible and thus sampled a wider range of conformational substates than the reduced protein . The increased rigidity of the reduced protein was also soon linked to an increase in the strength of the Met80 S–Fe bond relative to the oxidized state .…”
Section: Case Studiesmentioning
confidence: 99%
“…¶ Kharakoz and Mkhitaryan (1986). Ulmer and Kägi (1968); Patel and Canuel (1976). **Determined by comparing the separately prepared samples of the two protein forms (a large systematic error is possible).…”
mentioning
confidence: 99%
“…The term k3 is the rate constant for exchange once the labile site contacts the catalyst. This second step is primarily base catalyzed above pH 4 (McDonald & Phillips, 1973;Patel & Canuel, 1976;Englander & Kallenbach, 1984), but water itself can also react directly (Gregory et al, 1983). Acid catalysis occurs at lower pH (Perrin, 1989).…”
mentioning
confidence: 99%